Viral suppression in adolescents on antiretroviral treatment: review of the literature and critical appraisal of methodological challenges - Rashida A. Ferrand; Datonye Christopher Briggs; Jane Ferguson; Martina Penazzato; Alice Armstrong; Peter MacPherson; David A. Ross; Katharina Kranzer (2015)
Abstract Objective Medication adherence is often suboptimal for adolescents with HIV , and establishing correct weight‐based antiretroviral therapy dosing is difficult, contributing to virological failure. This review aimed to determine the proportion of adolescents achieving virological suppression after initiating ART . Methods MEDLINE , EMBASE and Web of Science databases were searched. Studies published between January 2004 and September 2014 including ≥50 adolescents taking ART and reporting on the proportion of virological suppressed participants were included. Results From a total of 5316 potentially relevant citations, 20 studies were included. Only eight studies reported the proportion of adolescents that were virologically suppressed at a specified time point. The proportion of adolescents with virological suppression at 12 months ranged from 27 to 89%. Conclusion Adolescent achievement of HIV virological suppression was highly variable. Improved reporting of virological outcomes from a wider range of settings is required to support efforts to improve HIV care and treatment for adolescents.